2017
DOI: 10.1038/s41598-017-03427-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an in vivo orally active dual-binding protein-protein interaction inhibitor targeting TNFα through combined in silico/in vitro/in vivo screening

Abstract: TNFα is a homotrimeric pro-inflammatory cytokine, whose direct targeting by protein biotherapies has been an undeniable success for the treatment of chronic inflammatory diseases. Despite many efforts, no orally active drug targeting TNFα has been identified so far. In the present work, we identified through combined in silico/in vitro/in vivo approaches a TNFα direct inhibitor, compound 1, displaying nanomolar and micromolar range bindings to TNFα. Compound 1 inhibits the binding of TNFα with both its recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…All interactions were hydrophobic, while interactions of the ligand with TNF residues Tyr59 and Tyr119 were identified as highly important for TNF inhibition [ 5 ]. Starting from the ligand SPD304 in 2005, several small molecule TNF inhibitors have been developed, including heterocyclic compounds, small organic ligands, natural products (NPs) and metal-complexed compounds [ 10 , 11 , 12 , 26 , 27 , 28 ]. Blevitt et al [ 29 ] discovered an inhibitor that forms an aggregating conglomerate, which antagonizes a protein subunit of the TNF trimer and alternates the quaternary structure of TNF upon binding.…”
Section: Introductionmentioning
confidence: 99%
“…All interactions were hydrophobic, while interactions of the ligand with TNF residues Tyr59 and Tyr119 were identified as highly important for TNF inhibition [ 5 ]. Starting from the ligand SPD304 in 2005, several small molecule TNF inhibitors have been developed, including heterocyclic compounds, small organic ligands, natural products (NPs) and metal-complexed compounds [ 10 , 11 , 12 , 26 , 27 , 28 ]. Blevitt et al [ 29 ] discovered an inhibitor that forms an aggregating conglomerate, which antagonizes a protein subunit of the TNF trimer and alternates the quaternary structure of TNF upon binding.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combined in silico/in vitro/in vivo screening approach, Mouhsine et al identified a new TNFα direct inhibitor, “Compound 1”, that binds to TNFα with high affinity at nM levels, and inhibits TNFα activity by effectively disrupting TNFα–TNFR binding. 53 This inhibitor prevents TNFα-induced apoptosis and NF-κB activation in L929 and HEK cell lines, respectively. It also showed in vivo activity in a hepatic shock model, although a high dose was needed due to low solubility and poor bioavailability.…”
Section: Small Molecule Tnfα Inhibitorsmentioning
confidence: 99%
“…Multiple approaches can be applied to achieve TNF-α inhibition by targeting any step of the above signaling cascades from plasma membrane to nucleus: (1) blocking the binding of stimuli to membrane receptors (e.g., TLR4 and MyD88) at the early stage, (2) interfering with an intracellular component of the cascade (e.g., IKK complex and JNK/ERK/p38 kinases ) to stop the signaling transduction, (3) suppressing the TNF-α nuclear transcriptional activity (e.g., DNA binding , ), and (4) directly targeting TNF-α or TNFR to inhibit its biological activity. Among the above signaling pathways, p38 MAPK inhibitors demonstrated efficacy in rodent UC models; however, the human clinical studies revealed only modest to nominal efficacy . Cumulative evidence indicated that UC is closely associated with MKK3, which is phosphorylated by upstream kinase MKKKs, such as TAK1 (TGF-β-activated kinase 1) .…”
Section: Introductionmentioning
confidence: 99%